Guidelines to implement add-on activities - Tesfaye, K.; Kalimuthu, S.; Cole, S.M.; Schmitter, P.; Casimero, M.; Aubert, C.; Assefa, B. (2024)
The scaling model of EiA is organized around demand-driven Use Cases, operating in a defined target area with a defined target public and focusing on the development, validation, and scaling of an agronomic solution, formulated through a Minimum Viable Product (MVP). The MVPs are expected to deliver agronomic gain for smallholder farmers in relation to (i) increased yield, profitability, and/or yield quality, (ii) climate change adaptation and reduced risk, (iii) increased resource use efficiencies, and (iv) improved soil health. These indicators are referred to as the ‘agronomic gain key performance indicators’ (KPIs), prioritized by EiA. To maximize the impact potential of EiA Use Cases across the KPI’s and across One CGIAR impact areasi, MVPs and MVP scaling strategies should be designed by: (i) addressing all key limitations to the delivery of the Use Case-specific agronomic gain indicators, (ii) understanding the farmer profiles or segments the Use Case is targeting, (iii) ensuring that all Use Cases are gender- and youth-responsive and explicit about climate change adaptation, (iv) understanding the current agronomic practices implemented by women, men and youth farmers in the target areas, and (v) assessing the ex-ante benefits of the final solutions when applied at scale. EiA has put in place teams of experts to support Use Case teams in considering above principles during the design, development, validation, and piloting of their MVPs. The support teams (‘Add-on teams’) are assembled around five specific topics of interest, so called ‘Add-on activities to the Use Cases’.